BODIPY‐Equipped Benzo‐Crown‐Ethers as Fluorescent Sensors for pH Independent Detection of Sodium and Potassium Ions. Issue 2 (8th November 2022) - Sprenger, Tobias; Schwarze, Thomas; Müller, Holger; Sperlich, Eric; Kelling, Alexandra; Holdt, Hans‐Jürgen; Paul, Jérôme; Martos Riaño, Vera; Nazaré, Marc
Abstract: Herein, we report on fluorescent probes which enable the selective quantification of Na + and K + in water by fluorescence enhancement (FE) independent of the pH value. These fluorescent probes, so called fluoroionophores, consist of benzo‐crown‐ether derivatives as ionophores, a benzo‐15‐crown‐5 (cf. 5 ) or a benzo‐18‐crown‐6 (cf. 6 ), respectively, to selectively bind either Na + or K + and a 4, 4‐difluoro‐1, 3, 5, 7‐tetramethyl‐4‐bora‐3a, 4a‐diaza‐s‐indacene (BODIPY) fluorophore. The fluoroionophore 5 shows a FE factor of 7.3 in the presence of 1000 mM Na + and 6 of 4.7 upon addition of 250 mM K + in an acidic environment. The dissociation constants ( K d ) for 5 +Na + is 276 mM and for 6 +K + is 18 mM enabling the fluorometric determination of biological relevant Na + or K + levels. The fluorescence intensities of 5 and 6 were not impacted over a broad range of proton concentrations (pH stable from 3.5 to 9.5) and by the presence of other biologically relevant cations. Abstract : Fluoroionophores : In this work, we introduce a highly Na + selective and Na + sensitive fluorescent probe, which show a similar Na + induced fluorescence enhancement over a broad pH value range from 3 to 10. Moreover, this probe is a universal fluorescent indicator for the analysis of Na + levels in biological settings.